THE ROLES OF TEACHER IN TEACHING ENGLISH BASED ON SCHOOL BASED CURRICULUM AT THEVIIIA GRADE OF SMPN I KADUR PAMEKASAN - R Agus Budiharto; Achmad Affandi (INTERAKSI : Jurnal Kependidikan, 2018)
The aim of this study are to know the role of a teacher in teaching English based on school based curriculum at junior high  school and to know the implementation of his role in teaching learning process. In this research the researcher take place at SMPN I Kadur Pamekasan, the approach of this research is qualitative while kind of research is descriptive, the data gotten by interview, observation and documentation. Those data is analyzed with analysis qualitative descriptive than the validity of data is checked by the persistence of observation a triangulation. The result of the research show that the English teacher implements six roles in teaching English, they are: As an informator, the English teacher gave some information to the students about the teaching process and the others information that needed by students. As an organizer, the English teacher made lesson plan, arrange the syllabus, designed the teaching process, chose and used the teaching method, and used media and learning source. As a motivator, the English teacher gave stimulation, motivation, and reinforcement to the students’ learning. As a director, the English teacher guided and directed the students’ learning activity appropriate the goal will be reached. As a facilitator, the English teacher gave facilitate to the students in teaching learning process. As an evaluator, the English teacher evaluated to the students achievement in academy aspect and their social attitude. Those roles will make the student be able to interest in English teaching learning process. The existence those roles will make English teacher easy to deliver the material will be given to the student in teaching learning process.